Tracing Activity Across the Whole Brain Neural Network with Optogenetic Functional Magnetic Resonance Imaging - Lee, Jin Hyung (Frontiers in Neuroinformatics, 2011)
Despite the overwhelming need, there has been a relatively large gap in our ability to trace network level activity across the brain. The complex dense wiring of the brain makes it extremely challenging to understand a specific set of neuron’s activity and their communication beyond a few synapses. Recent development of the optogenetic functional magnetic resonance imaging (ofMRI) provides a new impetus for the study of the brain circuit by enabling causal tracing of the brain circuit activity across the whole brain. Brain circuit elements can be selectively triggered based on their genetic identity, cell body location, and/or their axonal projection target with temporal precision while the resulting network response is monitored non-invasively with unprecedented spatial and temporal accuracy. With further studies including technological innovations to bring ofMRI to its full potential, ofMRI is expected to play an important role in our system-level understanding of the brain circuit mechanism.